Dynamic Mineralization: Low‐Temperature, Rapid, and Multidirectional Process to Encapsulate Polyether‐Ether‐Ketone with Carbonate‐Rich Hydroxyapatite for Osseointegration (Adv. Mater. Interfaces 15/2021). Issue 15 (11th August 2021) - Lui, Florence H. Y.; Mobbs, Ralph J.; Wang, Yu; Koshy, Pramod; Lucien, Frank P.; Zhou, Dewen; Sorrell, Charles C.
Abstract : Orthopaedic Implant Coatings In article number 2100333, Florence H.Y. Lui, Charles C. Sorrell, and co‐workers describe a dynamic mineralization method to encapsulate polyether‐ether‐ketone with carbonate‐apatite for osseointegration. The nature‐inspired process is simultaneously low‐temperature, rapid, and multidirectional, indicating suitability with a wide range of orthopaedic materials. A precursor CaCO3 layer is deposited by nacre‐inspired convective self‐assembly, followed by a travertine‐inspired cold sintering step. The CaCO3 is converted to carbonate‐apatite by dissolution‐recrystallization inspired by the hydrated layer of bone.